Status of Medicinal Plants Consumption by the Pharmaceutical Industries in Gujarat State - Singh, A. P.; Parabia, Minoo (Indian Forester, 2003)
The estimation of raw material consumed by the pharmaceutical industries in Gujarat State is studied. Survey in this regard made first time for Gujarat State. The baseline database is created for indigenous and imported as well as indigenous and cultivated , trees , shrubs , climbers , herbs and different crops used in Ayurvedic medicines. The consumption level for all the medicinal plants species is estimated which can be utilized by different authorities for different purposes. The species-specific and plant part-specific consumption status is also studied and discussed.